THE COLLABORATION BETWEEN KPU, DISABILITIES, AND MEDIA TO SOCIALIZE INCLUSIVE ELECTIONS FOR DISABILITIES IN SURABAYA - Hikmah, Nurul (Reflektika, 2025)
The purpose of this research is to analyse the challenges faced by voters with disabilities in the general elections in Indonesia and to explore the importance of collaborative governance in creating an inclusive election. This study employs a literature review method by collecting data from various sources, including journal articles and online publications. The analysis results indicate that voters with disabilities encounter multiple issues, such as the lack of integration of voter data, insufficient access to information, and difficulties in exercising their voting rights. Furthermore, collaboration between the General Election Commission (KPU) and disability organisations is crucial to provide the necessary assistive tools and training for election officials. This research concludes that implementing collaborative governance can enhance the participation of voters with disabilities and create a more inclusive election, allowing all citizens to participate fairly in the democratic process.